PROBLEMS OF FORMATION OF CONSOLIDATED FINANCIAL STATEMENTS IN UKRAINE AND WAYS OF ITS SOLUTION - Богданюк, Елена; Лебедько, Алена (SWorldJournal, 2021)
The need to submit consolidated financial statements in Ukraine is caused by the emergence of holding companies, concerns, other groups, as well as joint stock companies with a significant number of subsidiaries. However, despite the fact that a long time